Work Fatigue Among Emergency Department Nurses in Banjarmasin Hospitals - Hery Wibowo; Prayoga, Aditya Restu; Islamiyah; Fadli, Muhammad (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2025)
High levels of fatigue among nurses in the Emergency Department (ED) can lead to various negative consequences, including increased risk of errors, changes in physical and mental health, and decreased quality of care. This study aims to describe the level of fatigue among ED nurses in hospitals in Banjarmasin. A quantitative research method was employed using the KUPK2 questionnaire, administered to 35 respondents through a total sampling technique during June–July 2024. Data were analyzed using univariate tests to provide a comprehensive overview of fatigue levels. The results showed that the average work fatigue score among nurses was 26.49, which falls into the